2015
DOI: 10.1098/rspb.2015.0972
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriocin-mediated competition in cystic fibrosis lung infections

Abstract: Bacteriocins are toxins produced by bacteria to kill competitors of the same species. Theory and laboratory experiments suggest that bacteriocin production and immunity play a key role in the competitive dynamics of bacterial strains. The extent to which this is the case in natural populations, especially human pathogens, remains to be tested. We examined the role of bacteriocins in competition using Pseudomonas aeruginosa strains infecting lungs of humans with cystic fibrosis (CF). We assessed the ability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 43 publications
6
38
0
Order By: Relevance
“…Unlike the killing mechanism of pyocins S2 and S3, which depends on the FpvA ferripyoverdine receptors, the resistance mechanisms to pyocins S1 and AP41 are still unknown (Denayer et al ., 2007). Our data confirm that the resistance to pyocins mostly occurs via mechanisms independent from specific immunity genes (Ghoul et al ., 2015). The resistances to S1 and AP41 pyocins could be due to the loss of a membrane receptor that allows the entry of these toxins into the bacterial cell.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Unlike the killing mechanism of pyocins S2 and S3, which depends on the FpvA ferripyoverdine receptors, the resistance mechanisms to pyocins S1 and AP41 are still unknown (Denayer et al ., 2007). Our data confirm that the resistance to pyocins mostly occurs via mechanisms independent from specific immunity genes (Ghoul et al ., 2015). The resistances to S1 and AP41 pyocins could be due to the loss of a membrane receptor that allows the entry of these toxins into the bacterial cell.…”
Section: Resultssupporting
confidence: 89%
“…As we did not find any obvious receptor-encoding genes within the chromosomal region missing from the brown mutants, we speculated the presence within this region of a gene encoding a regulator which deletion abolishes or downregulates the production of a pyocin receptor. These results could indicate that the relative resistance to AP41 and/or S1-pyocins of the pyomelanin-producing mutants plays a key role in the survival of these adapted mutants in patients; in support of this concept, nearly all (98%) the clinical isolates of P. aeruginosa isolated from CF-patients have been observed to produce at least one S-pyocin (Ghoul et al ., 2015). However, we are aware that the pyocins that we did not test (S-pyocins S4, S5, S6, R-pyocin R4 and F-pyocins) could also play a role in bacterial competition.…”
Section: Resultsmentioning
confidence: 91%
“…Finally, we found that bacteriocin‐mediated inhibition occurs less frequently between coexisting isolates, suggesting bacteriocin production selects for genotypes resistant to local bacteriocin producers. The low levels of inhibition we observe between coexisting isolates could occur if (i) isolates interact more frequently with identical or closely related competitors, who produce similar bacteriocins and are thus resistant, or (ii) if unrelated isolates have evolved resistance to local bacteriocin producers (Kerr et al ., ; Ghoul et al ., ). These outcomes are not mutually exclusive: each of our sites is genotypically diverse, whereas many harbour a numerically dominant genotype, suggesting both processes may be important.…”
Section: Discussionmentioning
confidence: 97%
“…Bacteriocins (named pyocins) produced by Pseudomonas spp. have been extensively studied (8-12), but the isolation of a bacteriocin with broad-spectrum activity against multidrug-resistant (MDR) Pseudomonas has been rarely reported (13). …”
Section: Introductionmentioning
confidence: 99%